IMPLEMENTATION OF ESP32-CAM AND TELEGRAM BOT FOR AUTOMATIC CUSTOMER ARRIVAL DETECTION SYSTEM - Rayell Danish Bryo Kalesaran; Charlie William; Christie Redja; Endah Setyaningsih (TESLA: Jurnal Teknik Elektro, 2024)
This study discusses the development of an automated system for detecting customer arrivals using the ESP32-CAM device integrated with a Telegram bot. The system is designed to detect movement through a PIR (Passive Infrared) sensor, which automatically triggers the ESP32-CAM to capture images when activity is detected. The captured images are then sent via the Telegram bot to the mobile devices of staff or business owners. The detection algorithm starts with the initialization of the PIR sensor to monitor movement, then the ESP32-CAM automatically takes pictures when movement is detected. These images are then sent through the Telegram bot to the mobile devices. Testing was performed repeatedly, with measurements of optimal detection range, notification delivery speed, and a user satisfaction survey regarding the system. The results of the tests show that the ESP32-CAM and PIR sensor have an optimal detection range of 1 to 7.5 meters. However, testing was not conducted beyond 7.5 meters as the maximum distance of the room at the location is 7.5 meters. Additionally, the survey results indicate that users find the system easy to use and very helpful in improving service productivity. The research methodology involved system design, with stages ranging from design to the implementation of the automated customer arrival detection system. The hardware used includes the ESP32-CAM and PIR sensor, while the software focuses on configuring the Telegram bot as the communication medium. Implementation was carried out by integrating the hardware and software so that the system could function properly. Further testing was done to evaluate the reliability of the system, particularly in detecting movement and sending notifications with images. The improvement and follow-up plan includes enhancing the detection range of the PIR sensor, testing the system under various environmental conditions such as low light and larger areas, as well as developing facial recognition integration to improve the accuracy of customer detection. The conclusion of this study shows that the system works as intended, with the ESP32-CAM and PIR sensor having an optimal detection range of 1 to 7.5 meters. The system effectively detects customer arrivals and automatically sends images to the Telegram bot, enabling business owners to monitor activities remotely without physical presence, thereby improving response times and the quality of customer service Abstrak Penelitian ini membahas pengembangan sistem otomatis untuk mendeteksi kedatangan pelanggan dengan menggunakan perangkat ESP32-CAM yang terintegrasi dengan bot Telegram. Sistem ini dirancang untuk mendeteksi pergerakan melalui sensor PIR (Passive Infrared), yang akan memicu ESP32-CAM secara otomatis untuk mengambil gambar saat ada aktivitas terdeteksi. Gambar yang diambil kemudian dikirimkan melalui bot Telegram ke perangkat seluler staf atau pemilik usaha. Algoritma deteksi dimulai dengan inisialisasi sensor PIR yang memantau pergerakan, lalu ESP32-CAM secara otomatis mengambil gambar saat gerakan terdeteksi. Gambar tersebut kemudian dikirim melalui bot Telegram ke perangkat seluler. Pengujian dilakukan secara berulang dengan data pengukuran jarak optimal, kecepatan pengiriman notifikasi, serta survei kepuasan pengguna terhadap sistem ini. Hasil pengujian dari penelitian ini menunjukkan bahwa ESP32-CAM dan sensor PIR memiliki jangkauan deteksi optimal pada rentang 1 hingga 7,5 m. Namun, untuk jarak lebih dari 7,5 m, tidak dilakukan pengujian lebih lanjut karena jarak maksimum dari ruangan di lokasi adalah 7,5 m. Selain itu, survei menunjukkan bahwa pengguna merasa sistem ini mudah digunakan dan sangat membantu dalam meningkatkan produktivitas pelayanan. Metodologi penelitian berupa perancangan sistem, yang mempunyai tahapan, yaitu mulai dari perancangan hingga implementasi sistem deteksi otomatisasi kedatangan pelanggan. Perangkat keras yang digunakan meliputi ESP32-CAM dan sensor PIR, sementara perangkat lunak berfokus pada konfigurasi bot Telegram sebagai media komunikasi. Implementasi dilakukan dengan mengintegrasikan perangkat keras dan perangkat lunak agar sistem dapat berfungsi sebagaimana mestinya. Selanjutnya, pengujian dilakukan untuk mengevaluasi keandalan sistem, terutama dalam mendeteksi pergerakan dan mengirimkan notifikasi dengan gambar. Rencana perbaikan dan tindak lanjut meliputi peningkatan jangkauan deteksi sensor PIR, pengujian sistem pada berbagai kondisi lingkungan seperti pencahayaan rendah dan area yang lebih luas, serta pengembangan integrasi pengenalan wajah untuk meningkatkan akurasi deteksi pelanggan. Kesimpulan dari hasil penelitian ini menunjukkan bahwa sistem bekerja sesuai dengan tujuan, dengan ESP32-CAM dan sensor PIR memiliki jangkauan optimal pada rentang 1 hingga 7,5 m. Sistem ini terbukti mendeteksi kedatangan pelanggan dan mengirimkan gambar secara otomatis ke bot Telegram, memungkinkan pemilik usaha untuk memantau aktivitas dari jarak jauh tanpa kehadiran fisik, sehingga meningkatkan respons dan kualitas layanan pelanggan.